Data for: Ionic Liquid Conductivity Models by Symbolic Regression - Bengtsson, Isak; Johansson, Patrik (Chalmers University of Technology, 2026)
Two datasets with experimentally measured ionic conductivities for different ionic liquids (IL) are provided. The first one was measured in-house for a publication by Nilsson-Hallén et al. (2019), whilst the second one is a curated subset of the database ILThermo. In addition to the experimental data, a set of molecular descriptors are given for each IL. These were computed using the open-source software RDKIT and OpenBabel.

Två dataset med experimentellt uppmätta jonledningsförmågor för olika jonvätskor (IL) tillhandahålls. Det första mättes internt för en publikation av Nilsson-Hallén et al. (2019), medan det andra är ett kurerat urval från databasen ILThermo. Utöver experimentell data tillhandahålls även "molecular descriptors" för varje jonvätska. Dessa har beräknats med hjälp av open-source mjukvarorna RDKit och OpenBabel.
Data för: Ionic Liquid Conductivity Models by Symbolic Regression
Keywords: ionic conductivity; ionic liquids; jonvätskor; Atom and Molecular Physics and Optics; Atom- och molekylfysik och optik; Physical Chemistry; Fysikalisk kemi